2017
DOI: 10.3857/roj.2016.02054
|View full text |Cite
|
Sign up to set email alerts
|

Influence of jaw tracking in intensity-modulated and volumetric-modulated arc radiotherapy for head and neck cancers: a dosimetric study

Abstract: PurposeTo Study the dosimetric advantage of the Jaw tracking technique in intensity-modulated radiotherapy (IMRT) and volumetric-modulated arc therapy (VMAT) for Head and Neck Cancers.Materials and MethodsWe retrospectively selected 10 previously treated head and neck cancer patients stage (T1/T2, N1, M0) in this study. All the patients were planned for IMRT and VMAT with simultaneous integrated boost technique. IMRT and VMAT plans were performed with jaw tracking (JT) and with static jaw (SJ) technique by kee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…We found that the mean and maximal doses of OARs in JT plans were all lower than NJT plans with the same target coverage that is consistent with the results of other articles. 7 - 11 The transmission of Varian HD MLC is about 1.2% for 6MV, 12 and the jaw transmission is <0.5%, so it is easier to reduce the OAR dose with JT. For small lesions, the field size is small, so the leakage to the OARs is also small.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the mean and maximal doses of OARs in JT plans were all lower than NJT plans with the same target coverage that is consistent with the results of other articles. 7 - 11 The transmission of Varian HD MLC is about 1.2% for 6MV, 12 and the jaw transmission is <0.5%, so it is easier to reduce the OAR dose with JT. For small lesions, the field size is small, so the leakage to the OARs is also small.…”
Section: Discussionmentioning
confidence: 99%
“…The dosimetric influence of jaw tracking in IMRT and VMAT for head and neck cancer has been investigated and published in our previous study [1]. In this study, we would like to investigate the dosimetric influences of jaw tracking IMRT and VMAT compared to the static jaw IMRT and VMAT in the patients of carcinoma of the cervix, as an extension of our previous study.…”
Section: Introductionmentioning
confidence: 95%
“…In the standard static jaw (SJ) IMRT and VMAT delivery, the secondary jaws stay in fixed position and the MLC moves to modulate the intensity pattern of the photon beams to achieve a desired dose distribution. The typical MLC transmission of the Varian Millenium MLC ranges from 1.6% to 2.5% for the beam energies from 6 MV to 18 MV photon beams [1]. In 3dimensional conformal radiotherapy (3DCRT) with 15 MV four field box technique the average MU required is 228.9 ± 3.6 MU for 2 Gy per fraction according to our institutional data, this may vary depends upon the patient thickness and the photon beam energy used, whereas the average MU documented in this study for the static jaw IMRT and VMAT were 1573.6 ± 206.1 and 479.6 ± 124.1 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…8 Relative to previously used cone collimators, the shielding provided by the MLC, however, is not optimal due to interleaf leakage or transmission which contributes to the low dose to normal tissue. [9][10][11] Delivery of VMAT plans is conventionally performed with the LINAC secondary collimator jaws remaining static at the maximum aperture that the MLC achieves during treatment. 10,12 It is proposed that the interleaf leakage or transmission through the MLC, and hence the low-dose delivered to normal tissue, may be reduced through the implementation of jaw tracking.…”
Section: Introductionmentioning
confidence: 99%